2016
DOI: 10.1007/s12010-016-2208-3
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Heptapeptide with Tyrosinase Inhibitory Activity Identified from a Phage Display Library

Abstract: Peptidic inhibition of the enzyme tyrosinase, responsible for skin pigmentation and food browning, would be extremely useful for the food, cosmetics, and pharmaceutical industries. In order to identify novel inhibitory peptides, a library of short sequence oligopeptides was screened to reveal direct interaction with the tyrosinase. A phage displaying heptapeptide (IQSPHFF) was found to bind most strongly to tyrosinase. The inhibitory activity of the heptapeptide was evaluated using mushroom tyrosinase. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…This peptide was able to chelate copper ions, and molecular docking study demonstrated the formation of hydrogen bonds between IQSPHFF and tyrosinase: Lys229, Gly250, and Ser276. The safety of the peptide was proven by the evaluation at the concentration range of 4.5–1152.0 μmol/L toward A375 melanoma cells 51 …”
Section: Natural Peptidesmentioning
confidence: 99%
“…This peptide was able to chelate copper ions, and molecular docking study demonstrated the formation of hydrogen bonds between IQSPHFF and tyrosinase: Lys229, Gly250, and Ser276. The safety of the peptide was proven by the evaluation at the concentration range of 4.5–1152.0 μmol/L toward A375 melanoma cells 51 …”
Section: Natural Peptidesmentioning
confidence: 99%
“…23 Some synthetic short peptides appear to show inhibitory activity against tyrosinase. 4,7,24 Some oligopeptides 25,26 and squid collagen hydrolysate 27 that showed tyrosinase-inhibitory effects have been suggested as cosmetic agents. Bioactive peptides are small protein fragments that have biological activity after they are released from proteins by hydrolytic treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Histidine residues are present in peptides with high PPO inhibitory capacity, along with residues of phenylalanine, cysteine, tryptophan, tyrosine and arginine. The presence of phenylalanine residues (which are structurally similar to tyrosine, a PPO substrate) in the peptide chain would allow its accommodation and formation of a strong interaction with the active site of the enzyme, which would cause competitive inhibition (Puangphet et al 2015;Nie et al 2017). Fragments of proteins (peptides) containing cysteine and/or phenylalanine residues along with apolar amino acid residues, such as valine, alanine, leucine, histidine and tryptophan, had their inhibitory power increased, since hydrophobicity would facilitate their entry and obstruction on the site of PPO, since it is also apolar (Schurink et al 2007;Noh et al 2009;Campas-Ríos et al 2012;Nie et al 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The presence of phenylalanine residues (which are structurally similar to tyrosine, a PPO substrate) in the peptide chain would allow its accommodation and formation of a strong interaction with the active site of the enzyme, which would cause competitive inhibition (Puangphet et al 2015;Nie et al 2017). Fragments of proteins (peptides) containing cysteine and/or phenylalanine residues along with apolar amino acid residues, such as valine, alanine, leucine, histidine and tryptophan, had their inhibitory power increased, since hydrophobicity would facilitate their entry and obstruction on the site of PPO, since it is also apolar (Schurink et al 2007;Noh et al 2009;Campas-Ríos et al 2012;Nie et al 2017). Cysteine residues in these peptides probably follow a mechanism of action similar to that of sulfur compounds, such as sulfites and L-cysteine, which participate in the stabilization of o-quinones via nucleophilic addition or reduction reactions (Campas-Ríos et al 2012;Puangphet et al 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation